2014
DOI: 10.1523/jneurosci.4064-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Potentiation at Cerebellar Parallel Fiber–Purkinje Cell Synapses Requires Presynaptic and Postsynaptic Signaling Cascades

Abstract: Long-term depression (LTD) and long-term potentiation (LTP) at cerebellar parallel fiber-Purkinje cell (PF-PC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 68 publications
5
91
2
Order By: Relevance
“…Thus, local E2 could contribute to synaptic plasticity through pathways associated with rapid and moderate increases in calcium concentration that have been shown to be responsible for LTP in PCs (Coesmans et al 2004;Jorntell and Hansel 2006;Nilsen et al 2002;Wang et al 2014). Consistent with this idea, E2 may facilitate LTP induction as well as prevent inappropriate calcium increments that would switch the LTP into LTD (Fig.…”
Section: Possible E2 Functions On Pf Plasticity In Adult Cerebellumsupporting
confidence: 53%
“…Thus, local E2 could contribute to synaptic plasticity through pathways associated with rapid and moderate increases in calcium concentration that have been shown to be responsible for LTP in PCs (Coesmans et al 2004;Jorntell and Hansel 2006;Nilsen et al 2002;Wang et al 2014). Consistent with this idea, E2 may facilitate LTP induction as well as prevent inappropriate calcium increments that would switch the LTP into LTD (Fig.…”
Section: Possible E2 Functions On Pf Plasticity In Adult Cerebellumsupporting
confidence: 53%
“…The defect in long-term depression by cPLA 2 ␣ defi ciency or COX-2 inhibition attenuates optokinetic eye movement adaptation, suggesting that cPLA 2 ␣ -regulated long-term depression is important for motor learning. Long-term potentiation is also important for motor learning and a recent report found that long-term potentiation in cerebellar parallel fi ber-Purkinje cell synapses is abolished in cPLA 2 ␣ KO mice ( 170,171 ).…”
Section: Nervous Systemmentioning
confidence: 99%
“…Thus, we may speculate that, in these individuals, non-modulated endothelial NO release and diffusion to the extracellular compartment could be detrimental for cerebellar maturation. In fact, NO is neurotoxic under conditions of excessive production [35]; in particular, abnormal NO availability impairs the regulation of granule maturation and, consequently, of the activity of Purkinje cells [36].…”
Section: Discussionmentioning
confidence: 99%